Optimizing performance of a reduced switch multi‐level inverter with moth‐flame algorithm and SHE‐PWM - Shanono, Ibrahim Haruna; Abdullah, Nor Rul Hasma; Daniyal, Hamdan; Muhammad, Aisha (Journal of engineering (Stevenage, England), 2023)
Multi‐level inverters are widely used in high‐voltage and high‐power applications due to the increasing demand for renewable energy. This study proposes a novel single‐phase reduced switch multi‐level inverter topology that generates 11 levels of output voltage steps, operates in asymmetric mode, and uses fewer power electronic switches with efficient switching control. To optimize the inverter's performance, Moth Flame Optimization (MFO), Particle Swarm Optimization (PSO), and Whale Optimization Technique (WOA) are utilized to apply the selective harmonic elimination technique. The proposed circuit is implemented in PSIM software using optimized switching angles, and the fitness functions and switching angles for the three optimizers are evaluated and reported. The inverter's performance at optimal modulation points for the three optimizers is computed and analyzed, with the Total Harmonic Distortion (THD) measured at 0.82 modulation point before and after filtering. Results show that MFO outperforms PSO and WOA with the lowest THD values of 0.85% and 0.78%, respectively; therefore, complying with the IEEE 519 standard. The experimental validation of MFO's superiority is performed using the Typhoon HIL‐402 hardware device. This study provides a promising solution for the design and optimization of multi‐level inverters, paving the way for more efficient and reliable renewable energy systems. A novel single‐phase reduced switch multi‐level inverter topology with efficient switching control that generates 11 output voltage steps in asymmetric mode is proposed. Moth Flame Optimization (MFO), Particle Swarm Optimization (PSO), and Whale Optimization Technique (WOA) are utilized to optimize the inverter's performance. Results show that MFO performs best, followed by PSO and WOA, and the superiority of MFO is verified experimentally using the Typhoon HIL‐402 hardware device.